Quorum sensing inhibitors from marine bacteria Oceanobacillus sp. XC22919. Issue 12 (18th June 2019) - Chen, Xiaochun; Chen, Jianwei; Yan, Yinchun; Chen, Su; Xu, Xuewei; Zhang, Huawei; Wang, Hong
Abstract: In this study, three active compounds isolated from Oceanobacillus sp. XC22919 were identified as 2-methyl- N -(2′-phenylethyl) butyramide (1 ), 3-methyl- N -(2′-phenylethyl)-butyramide (2 ) and benzyl benzoate (3 ), and were first reported to exhibit the apparent quorum sensing inhibitory activities against C. violaceum 026 and P. aeruginosa . Compounds1 –3 inhibited violacein production of C. violaceum 026 by 10.5–55.7, 11.2–55.7, and 27.2%–95.7%, respectively, and inhibited pyocyanin production of P. aeruginosa by 1.7–50.8, 39.1–90.7, and 57.2%–98.7%, respectively. The azocasein-degrading proteolytic rates of P. aeruginosa were observed by 13.4–31.5, 13.4–28.8, and 11.3%–21.1%, respectively. With respect to elastase, the range of inhibition of activity of compounds1 –3 was 2.1–30.3, 4.2–18.2, and 8.9%–15.7%, respectively. Compounds1 and3 also showed a concentration-dependent attenuation in biofilm formation, with the maximum of 50.6% inhibition, and 37.7% inhibition at 100 μg/mL, respectively. Abstract :